(untitled) (Revista Iberoamericana de Bioética, 2024)
Faced with the COVID-19 pandemic, the need for attention to people living in vulnerable situations increased; however the principles of bioethics, justice and equity are there to strengthen the protection of life, and the ethics of care would, in turn, be the basis for the implementation of public policies. The effects of the COVID-19 pandemic on the elderly population were analyzed, considering their vulnerabilities from the perspective of bioethics. This is a theoretical essay based on an integrative review of the literature on bioethics and vulnerability in the elderly in the face of the COVID-19 pandemic. The results were discussed from a bioethics perspective. It is hoped that this essay will contribute to reflections on this harsh reality, which is damaging and generates suffering for the elderly, because only through a new structure between political, social and civilizing processes will it be possible to conceive a society that is more dignified and humane.